2017
DOI: 10.1002/elan.201700520
|View full text |Cite
|
Sign up to set email alerts
|

Batch Injection Analysis‐Multiple Pulse Amperometric Fingerprint: A Simple Approach for Fast On‐site Screening of Drugs

Abstract: In this work, the association of batch injection analysis with multiple pulse amperometric detection (BIA‐MPA) is presented as a new approach to obtain drugs fingerprints. To illustrate the potential of this screening method, tablets containing sildenafil as the active substance were used. Here, a sequence of three potential pulses as a function of time (+1.3, +1.6 and +2.1 V) were applied on a boron‐doped diamond electrode while reproducible injections were performed in a BIA cell (wall jet configuration). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The BIA-MPA system was used successfully in the simultaneous determination of nimesulide and paracetamol (Pereira et al, 2013), codeine and diclofenac (Gimenes et al, 2013), propranolol and hydrochlorothiazide (Gimenes et al, 2014), diphenhydramine and 8-chlorotheophylline (dimenhydrinate) (Freitas et al, 2014), sulfamethoxazole and trimethoprim (Pereira et al, 2015), captopril and hydrochlorothiazide (Gimenes et al, 2015), amlodipine and atenolol (Silva et al, 2016), pheniramine and naphazoline (Oliveira et al, 2018b), or chlorpheniramine and naphazoline (Oliveira et al, 2018b). The possibility of selective determination of sildenafil (Garcia Cardozo et al, 2017) using the MPA technique was also recently shown. It is important to mention that all works employed a cathodically pretreated BDD electrode.…”
Section: Bdd Electrode Coupled To Bia Systemsmentioning
confidence: 98%
“…The BIA-MPA system was used successfully in the simultaneous determination of nimesulide and paracetamol (Pereira et al, 2013), codeine and diclofenac (Gimenes et al, 2013), propranolol and hydrochlorothiazide (Gimenes et al, 2014), diphenhydramine and 8-chlorotheophylline (dimenhydrinate) (Freitas et al, 2014), sulfamethoxazole and trimethoprim (Pereira et al, 2015), captopril and hydrochlorothiazide (Gimenes et al, 2015), amlodipine and atenolol (Silva et al, 2016), pheniramine and naphazoline (Oliveira et al, 2018b), or chlorpheniramine and naphazoline (Oliveira et al, 2018b). The possibility of selective determination of sildenafil (Garcia Cardozo et al, 2017) using the MPA technique was also recently shown. It is important to mention that all works employed a cathodically pretreated BDD electrode.…”
Section: Bdd Electrode Coupled To Bia Systemsmentioning
confidence: 98%